N4,N6-Dimethyl-N4,N6-diphenylpyrimidine-4,5,6-triamine - Fuqiang Shi; Li-Hong Zhu; Li Mu; Long Zhang; Ya-Feng Li (Acta Crystallographica Section E, 2011)
In the title compound, C18H19N5, the pyrimidine ring makes dihedral angles of 56.49 (9) and 70.88 (9)° with the phenyl rings. The dihedral angle between the two phenyl rings is 72.45 (9)°. No significant intermolecular interactions are observed in the crystal structure.